A social problem analysis of the 1993 Brady Act and the 2022 Bipartisan Safer Communities Act - Ziminski, Devon (Frontiers in Public Health, 2024)
Safer Communities Act (BSCA).-Summative content analysis was used to explore how the social problem of firearm violence was outlined in both policies, with the goal of extracting the social issue's definition from the policies' approaches to solving it. -Both policies do not outline the various types of firearm violence, nor the disproportionate effect of firearm violence on certain populations. -This work informs the role of federal policy in defining and monitoring firearm violence as a public health issue, identifying both individual and structural risk and protective factors from an asset-based lens, and allocating preventative efforts in communities that are most affected.